Motion control for a walking companion robot with a novel human–robot interface. (8th September 2016) - Lv, Yunqi; Gao, Xueshan; Dai, Fuquan; Liu, Yubai; Shahzad, Adil; Zhao, Jun; Zhang, Tong
A walking companion robot is presented for rehabilitation from dyskinesia of lower limbs in this article. A new human–robot interface (HRI) is designed which adopts one-axis force sensor and potentiometer connector to detect the motion of the user. To accompany in displacement and angle between the user and the robot precisely in real time, the common motions are classified into two elemental motion states. With distinction method of motion states, a classification scheme of motion control is adopted. The mathematical model-based control method is first introduced and the corresponding control systems are built. Due to the unavoidable deviation of the mathematical model-based control method, a force control method is proposed and the corresponding control systems are built. The corresponding simulations demonstrate that the efficiency of the two proposed control methods. The experimental data and paths of robot verify the two control methods and indicate that the force control method can better satisfy the user's requirements.